PENGARUH JOB SECURITY TERHADAP PERSEPSI KESELAMATAN PADA PEKERJA KONSTRUKSI LAPANGAN DI INDUSTRI MINYAK DAN GAS - Bagos, Bagos Armansyah; Fitri Nugraheni (Universitas Muhammadiyah Surabaya, 2024)
Construction projects are activities that are prone to work accidents, so work safety management is needed to prevent work accidents. One of the factors that greatly influences the perception of work safety is the job security. The aim of this research is to identify job security factors and safety perceptions and analyze the influence of the relationship between job security and the perception of safety among field workers in the oil and gas industry, especially in the Riau province work area. The respondents were field workers and numbered 106 people. The research methods used are qualitative and quantitative. There were respondents who stated that the implementation of work safety was very high, but several dimensions such as sustainable salary increases were still not good (34.91%) and respondents stated that understanding and implementation of the perception of safety was very high. The results of the linear regression test show that job security has a positive and significant effect on the perception of safety among field construction workers, where job security contributes to the perception of safety by 21.5%. The more workers do not fulfill job security, the less workers will care about the perception of safety which can lead to not creating a good safety climate and increasing work accidents